Valkyria Chronicles Game and the â€œCuteâ€ Memory of War - Iskandar Zulkarnain; Otniel Joviand Christiandrew (Journal of Games, Game Art, and Gamification, 2023)
In this article we analyzed digital games as a mode of memory production and preservation especially in the genre of World War II games. Using a Japanese-produced PS3 game, Valkyria Chronicles (2008), we demonstrated the ideological aspects of this type of games in (re)shaping the memory of the World War II through what we called â€œallegorithmic memoryâ€ process. Borrowing from Alexander R. Gallowayâ€™s conception of â€œallegorithm,â€ we argued that the combination of narrative allegory and gameplay algorithm in Valkyria Chronicles has produced a â€œcuteâ€ perspective on the memory of World War II that is closely tied to the historical role of Japan during the War. Set in an alternate 1930s Europe, the game combined the collective memory of Holocaust with an atypical representation of World War II in its allegorithmic structure. We argued that this combination has produced a double screen memory that attempted to invite a shared affection in dealing with Japanese traumatic memory of World War II. In conclusion, our article demonstrated the capacity of digital games as a culturally-specific site of memory production and preservation offering a complex combination of recycled and new perspective of World War II.